ANALISIS PERENCANAAN STARTUP “EVERYYOUTH BEAUTY” - Chinta Dwi Cahyana; Indah; Delia Anggraini; Elya Agustina; Jerry Pranata Ardya; Tiara Fitari (Universitas Sarjanawiyata Tamansiswa, 2024)
Every Youth Beauty is a business that focuses on beauty products designed to support the skin care and beauty needs of the younger generation. The products offered by Every Youth Beauty are developed with high quality ingredients that are safe and skin friendly, and adapted to the trends and preferences of active and dynamic young consumers. By prioritizing innovation and attractive packaging, Every Youth Beauty is committed to providing effective, safe and affordable beauty care products for young customers who care about the health of their skin and appearance. kata kunci : sustainable beauty products, millennial consumption in beauty industry, Indonesia beauty industry growth